2007
DOI: 10.1007/s12034-007-0007-8
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of indigo carmine dye using TiO2 impregnated activated carbon

Abstract: The photocatalytic degradation of indigo carmine dye was studied using hydrothermally prepared TiO 2 impregnated activated carbon (TiO 2 : AC). A comparison between the degradation of the indigo carmine dye using commercial TiO 2 and TiO 2 : AC revealed the efficiency of the title compound. The degradation reaction was optimized with respect to the dye concentration and catalyst amount. The reduction in the chemical oxygen demand (COD) revealed the mineralization of dye along with colour removal. The active co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(72 citation statements)
references
References 16 publications
6
64
0
2
Order By: Relevance
“…But, the adsorbed dye molecules are not degraded immediately, because the intensity of the light and the amount of catalyst is constant and also, the light penetration will be less. Also, with increase in dye concentration, the solution becomes more intense coloured and the path length of the photons entering the solution is decreased thereby, fewer photons reached the catalyst surface [38].…”
Section: Impedance Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…But, the adsorbed dye molecules are not degraded immediately, because the intensity of the light and the amount of catalyst is constant and also, the light penetration will be less. Also, with increase in dye concentration, the solution becomes more intense coloured and the path length of the photons entering the solution is decreased thereby, fewer photons reached the catalyst surface [38].…”
Section: Impedance Studiesmentioning
confidence: 99%
“…Several studies have indicated that, photocatalytic rate initially increases with catalyst loading and then, decreases at high values because of light scattering and screening effects [38,48].…”
Section: Effect Of Catalyst Loadingmentioning
confidence: 99%
“…The composite TiO 2 /carbon is a potential photocatalyst in the purification of water because of the high adsorption ability of porous carbon and because carbon doping will narrow the bandgap, producing the active catalyst under visible light [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…While 50% ethanol can be used as a liquid medium in the 1 To whom any correspondence should be addressed. arc discharge process, TiO 2 /C nanocomposites produced via arc discharge in 50% ethanol do not disperse well in water [5]. To enhance the surface hydrophilicity of the nanocomposite, acetic acid was added to the ethanol liquid medium to provide attachment of the oxygen-containing functional group.…”
Section: Introductionmentioning
confidence: 99%
“…Physical methods are effective but have high post operation costs. Chemical methods result in harmful byproducts (Spagni A et al 2010 Subramani et al 2007). Methylene blue is one among the common dyes found in dyeing industry effluent few researchers are worked on methylene blue degradation by nano TiO 2 .…”
Section: Introductionmentioning
confidence: 99%